Does digital finance affect the quality of economic growth? Analysis based on Chinese city data - Liu, Tinghua; Hu, Mengyuan; Elahi, Ehsan; Liu, Xiao (Frontiers in Environmental Science, 2022)
The study used the entropy weight TOPSIS method to construct a comprehensive index system of economic growth quality and tested the mechanism of digital finance on economic growth quality. From 2011 to 2019, the panel data of 272 cities in China were collected. The study found that digital finance can promote the quality of China's economic growth in the long run, and the effect was more significant in less developed regions. The digital finance coverage, depth of use, and degree of digitalization had a significant impact on the quality of economic growth. The mechanism showed that digital finance can promote the quality of economic growth by promoting and upgrading industrial structure. In addition, we used the threshold model to test the non-linear relationship between digital finance and the quality of economic growth. Furthermore, the results showed that when digital finance was at a low level, it can hinder the improvement of economic growth quality. As digital finance developed further, it had a significant effect on the quality of economic growth and this effect gradually slowed down. Moreover, we found that digital finance played a more significant role in promoting the quality of economic growth in central and western regions and areas where traditional finance was underdeveloped. The conclusion of this study can provide reliable empirical evidence and policy enlightenment for the country to further promote high-quality economic development.